Caracterização da impressão digital do óleo derramado no litoral cearense em 2019 e 2022 usando técnicas analíticas de alta resolução. Uma abordagem geoquímica ambiental forense - Azevedo, Rufino Neto Andrade de (2023)
At the end of 2019, the northeastern coast was impacted by the arrival of spilled oil, reaching more than 3,000 km of coastline. This event was considered the largest spill in tropical environments in South America, causing social, economic and ecological impacts. In January 2022, new records of the presence of oil were reported on Ceará beaches, with approximately 8,000 liters of oil being collected along an extension of 400 km of the coast. The objective of this work was to investigate whether there is a geochemical correlation between the oils found on the beaches of Ceará in the events of 2019 and 2022. Oil samples were collected from different beaches on the east coast of the state between 2019 and 2022. The geochemical profile was characterized by aliphatic hydrocarbons (n-alkanes, pristane, phytane, hopanes and steranes) by GC-DIC and GC x GC-DIC and the polar acidic and basic compounds were analyzed by FT-ICR MS. The results obtained show a similar CG-DIC profile between the 2019 and 2022 oils, with n-alkanes ranging from n-C17 to n-C32 and the isoprenoids (pristane and phytane) present in low abundance or absent, in addition to the expressive presence from the MCNR. Analyzes of biomarker ratios indicated a similar geochemical profile between the 2022 samples, with DVPR values less than 7%. However, these oils have different biomarker profiles than the 2019 oils, which was directly reflected in the high values of DVPR, greater than 7% and above 40% in four of the twelve ratios calculated for all oils, thus indicating a different origin between these sets of oils. The FT-ICR analyseszes also us allowed to differentiate the 2019 and 2022 oils, in which the 2022 oils are richer in acidic sulfur compounds and the 2019 oils are richer in basic compounds of classes N2 [H], NS [H] and NS2 [H]. Regarding the geochemical analyses, the CPI ratio values close to 1 indicate that the 2019 and 2022 oils are mature. In addition, the 2019 oil contains marine organic matter and the 2022 oil was generated from marine carbonate source rocks. Regarding weathering effects, the absence of low molecular weight n-alkanes (<n-C17) indicated the evaporation process in the 2019 and 2022 oils. Values lower than 1 for the Pr/n-C17 and Fit/n ratios -C18 indicated that biodegradation was not as effective. The presence in high abundance of the oxygenated classes (O3, O3S, O4, O4S, O5 and O5S) indicated that photooxidation was more active in the 2022 oils; for the 2019 samples, the absence of more oxygenated classes (O4 and O5) indicated that photooxidation was not as active, but biodegradation.